Online certificate injection system - Mohd. Nor Haizam Samsun Baharun, author (Kuala Lumpur : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer - Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2005